PENGARUH PROMOSI PENJUALAN, PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP KEPUTUSAN MENGGUNAKAN TRANSPORTASI ONLINE (STUDI PADA PENGGUNA UBER DI SURABAYA PUSAT) - FATUH, MIYATUL (Jurnal Ilmu Manajemen (JIM), 2017)
The rapid and sophisticated technology development has change the lifestyles. The development of technology makes the business of creating internet-based transport services application one is the emergence of online taxi transportation business services. The existence of online taxi turned out to provide solutions and answer the various public concerns about public transportation services.’The’purpose’of ‘this’study’is’to analyze and discuss’the’effect’of sales promotion,’perceived’ease’of’use’and’perceived’usefulness’to’the decision’to’use online transportation at Uber company. Respondents in this study were Uberx users who made their own bookings with the age limit of 18-55 years and people who have used and ordered Uberx service more than once. In this study the number of samples taken as much as 220 respondents. Sampling method is nonprobability sampling and sampling technique using judgmental sampling. The data collection technics used in this study were questionnaires that were analyzed using Likert scale. Data analysis technique used multiple linear regression analysis with SPSS 18 program.The results of this study indicate that there is influence sales promotion, perceivedleaselofluseland perceive. usefulnessl tolthe decisionltoluse online transportation. Keywords: Sales Promotion,iPerceivediEaseiofiUse,iPerceivediUsefulness, Purchasing Decision